Intercultural communication experiences among students and teachers: implication to in-service teacher professional development - Othman, Azam; Ruslan, Norbaiduri (Emerald Group Holdings Ltd., 2020)
Purpose This paper aims to present the qualitative findings on students' and teachers' experiences in communicating and interacting with students and teachers from different ethnic backgrounds in the Malaysian vision schools initiative. Design/methodology/approach Face-to-face interviews were conducted involving 15 informants comprising of three headteachers, three teachers and nine students. The interviews centred on the informants' experiences and views living and experiencing the reality of the vision schools which is comprising three major races; Malays, Chinese and Indians; which is represented by the three school types which are a national school, Chinese vernacular and Indian vernacular schools. Findings The interview data revealed that the intercultural communication in the vision schools had triggered intercultural understanding and awareness of cultural diversity in the schools. However, the interview data with experienced teachers showed some drawbacks of the intercultural dynamics at the school complex. Among the weaknesses were the absence of structured and formal training on intercultural and multicultural education, lack of trust and poor social skills which may have hindered effective intercultural communication from taking place. Originality/value This study presents the informants' experiences and views on the reality of intercultural interaction among students and teachers in the context of the Malaysian vision school initiative